2022
DOI: 10.1002/pc.26914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyamide 12 and chain extender on the properties of microcrystalline cellulose reinforced polyamide 11 composites

Abstract: In the present study, polyamide 12 (PA12) and 2,2′‐(1,4‐phenylene)bis(2‐oxazoline) (PBO) were used to modify polyamide 11 (PA11), and then microcrystalline cellulose (MCC) reinforced PA11 composites was prepared via hot pressing. The results showed that the thermoplastic elastomer PA12 was in favor of the toughness of the composites, 12% PA12 increased the impact strength by 53%. The molecular chains of PA11/PA12 blends were extended by PBO, and then had positive effects on the mechanical properties, as eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Polyamide is emerging as a potential choice due to its strong molecular polarity and hydrogen bonding interactions. [ 4,9–11 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyamide is emerging as a potential choice due to its strong molecular polarity and hydrogen bonding interactions. [ 4,9–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide is emerging as a potential choice due to its strong molecular polarity and hydrogen bonding interactions. [4,[9][10][11] Currently, type IV vessels have a high failure rate of the liner and debonding between the thermoplastic liner and CFRP. [12] Multiple layers of CFRP are wound around the thermoplastic liner to support it.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These characteristics stem from the existence of segmented hard phases primarily composed of polyamide segments and soft phases mainly comprising soft segments, such as poly(tetramethylene glycol) (PTMG), at the nanoscale. TPAEs incorporating longalkyl polyamides, such as PA11 [4,5] and PA1012, [6] as hard segments, have undergone extensive study and found applications in diverse fields, including the automotive and textile industries. However, TPAEs featuring PA6 as hard segments have received limited attention due to the challenges associated with facile synthesis and melt-processing methods such as melt spinning.…”
Section: Introductionmentioning
confidence: 99%